1973
DOI: 10.1159/000271284
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Continuity of Interests and Activities during Adolescence

Abstract: Dimensional continuity was examined longitudinally at grades 7,9, and 11 using an inventory of social, academic and recreational activities administered to male and female dents. Indices indicating degree of factor presence, overall similarity of loading patterns, and structural stability of factors shown to result in a transitional’ shift’ or discontinuity, its locus at the time of high school entry (i.e., 9th grade). Although the finding was applicable to either sex, the nature of the discontinuity differed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…It is better to construct an instrument that includes activities relevant to children’s lives—activities which they engage in and have the necessary experience to accurately assess. For research in which interests have been assessed through familiar activities, the structure of interests in children has been found to differ from that of adults ( Dusek, Kermis, & Monge, 1979 ; Freeberg & Rock, 1973 ; Tyler, 1955 , 1956 ; Zbaracki, Clark, & Wolins, 1985 ).…”
Section: Assessment Of Interests In Childhood and Adolescencementioning
confidence: 99%
“…It is better to construct an instrument that includes activities relevant to children’s lives—activities which they engage in and have the necessary experience to accurately assess. For research in which interests have been assessed through familiar activities, the structure of interests in children has been found to differ from that of adults ( Dusek, Kermis, & Monge, 1979 ; Freeberg & Rock, 1973 ; Tyler, 1955 , 1956 ; Zbaracki, Clark, & Wolins, 1985 ).…”
Section: Assessment Of Interests In Childhood and Adolescencementioning
confidence: 99%
“…Differences in relations among behaviors at different life phases would be evidence of change in organization (cf. Freeberg & Rock, 1973, as an example of this approach with young and old adolescents). Another approach to the question of organization would be to examine the correlates of clinical problems (cf.…”
mentioning
confidence: 99%
“…(2) Certain common factors emerge not only in the adult work (Strong, 1968;Kuder, 1977;Guilford et al, 1954), but in work with adolescents (Dusek et al, 1979;Freeberg and Rock, 1973) and even children as Tyler (1951) found differences in children who preferred outdoor play, indoor play, paper-pencil-crayon play or helping adults.…”
Section: Discussionmentioning
confidence: 99%
“…Dusek et al's (1979) research demon strates that children's interests change with age at a time that fits Piaget's theory. The research of Freeberg and Rock (1973) and Stone and Barker (.1939) also fits such a framework.…”
Section: Theoretical Formulationmentioning
confidence: 92%
See 1 more Smart Citation